Enhancing the Academic Portfolio – Systems Engineering Research & Teaching for Universities. Issue 1 (16th August 2018) - Kossmann, Mario
Abstract: Many universities across the globe have well established Systems Engineering (SE) courses and academic degrees, covering continuous professional studies for both the industry and the public sectors, undergraduate and postgraduate programs including research degrees at master and doctorate levels. Some universities even have world‐class reputation for the excellence they demonstrate in SE research & teaching. However, there are still many universities worldwide that offer courses in traditional fields of Engineering but not yet in SE, let alone specific SE degrees or qualifications. Given that SE is essential for the development and in‐life support of systems, even more so with the increasing levels of complexity of today's and tomorrow's systems and Systems of Systems (SoS), it seems urgent and important for such universities to consider an extension of their academic portfolio. This paper briefly discusses the justifications for explicitly including SE in the curriculum of Engineering focused universities, and provides insight into one possible way of enhancing the successful establishment of SE as part of the academic portfolio – via developing and maintaining an SE domain ontology. The generic ontology 'SERaT4Ac' (SE Research and Teaching for Academia) that is specified in the 'ontology web language' (OWL) is presented and specific aspects of the ontology are explained using typical examples. This proposed domain ontology represents an integrated model of what a university should consider and manage over time regarding their SE related activities. It could (and would have to) be instantiated for the context of a given university to directly help them extend their academic portfolio; but it may also be useful for universities with a well‐established SE curriculum.